The Relationship between Fishermen Educational Level and Fishermen Knowledge Of Environmentally Friendly Fishing Gear In Cilincing Village, North Jakarta - KurniawatI, Evy; Isfaeni, Hanum; Komala, Ratna (Universitas Negeri Jakarta, 2015)
Fishermen plays an important role in the fisheries sector specifically for fishing gear. fishermen knowledge about environmentally friendly fishing gear expected to preserve the ecosystem and fish habitat. The result of this research is to know the relationship between fishermen educational level and fishermen knowledge about environmentally friendly fishing gear in Cilincing Village, North Jakarta. This research conducted in Cilincing Village on May 2014. The method in this research is descriptive correlational with technical survey. Populations are determined by purposive sampling. Samples were taken by simple random sampling with 60 fishermen sample. The instrument used was a questionnaire about the environmentally friendly fishing gear with 3 alternatives answer. The result shows that the highest value obtained was 60 – 72 and the lowest was 6 – 18. Analyzed data using Rank-Spearman. The result of this research shows indicated an relationship between fishermen educational level and fishermen knowledge about environmentally friendly fishing gear in Cilincing Village, North Jakarta with correlation value of 0,385.